ALFABETIZAÇÃO DE JOVENS E ADULTOS: investigando a Jornada de Alfabetização do Maranhão: “Sim, eu Posso!” - Círculo de Cultura no Município de Governador Newton Bello. - ARAUJO, Simone Costa Miranda (2021)
This work consists of qualitative research that discusses the Youth and Adult Literacy developed in the first phase of the Maranhão Literacy Journey: “Yes, I can!” – Culture Circle, held in the municipality of Governador Newton Bello – MA. Its general objective is to analyze the learners’ literacy process in the “Yes, I can!” Journey in the municipality of Governador Newton Bello, considering the contributions of Literacy Teachers and Class Coordinators. It understands the “Yes, I can!” Literacy Journey – Culture Circle as one of thirteen actions that emerged from the Programa Escola Digna (Decent School Program) – originating from the Plano de Ação Mais IDH (“More HDI” Action Plan), organized in 2015 to accomplish the goal of elevating the HDI in the most deprived municipalities of the state. The “Yes, I can!” Literacy Journey – Culture Circle aims to provide literacy, increase employability and income, and provide access to the digital world for young people and adults living in the Municipalities with lower HDI in Maranhão state. However, the scope of this study focuses on the literacy developed in the first phase of the Journey in the Municipality of Governador Newton Bello. For the analysis purposes, we considered the propositions and goals of the Journey referring to literacy, expressed in the documents that guide it and the Literacy Teachers and Class Coordinators positioning. The research is grounded on the thoughts of Arroyo (2011), Freire (1996; 2011), Soares (1999), Feitosa (2020), Bardin (1977; 2006), Brandão (2006), Díaz (2005), Di Pierro (2000; 2005), Gondim (2011), and documents as Laws (nº 9.394, de 20/12/96; nº 13.005, de 25/06/14; nº 10.099, de 11/06/14, Lei 10.172, de 9/01/01), Resolution nº 02/2011 - CEE/MA; Decree n° 30.612, de 02/01/15 and CEB Report nº 11/2000 that addresses the National Curriculum Guidelines for Youth and Adult Education (YAE), as well as the “More HDI” Action Plan, National Education Plan (NEP), State Education Plan (SEP 2013-2023), besides School Census (2010). The methodological conduction is based on Laurence Bardin (2011) and other authors that work in the content analysis perspective, used for data analysis and interpretation. Considering the exceptionality context provoked by the Covid-19 pandemic, the contact with research participants happened in the remote mode, with the use of Information and Communication Technology (TDIC), with a recording strategy in these moments. The participants in this research were 03 Class Coordinators and 08 Literacy Teachers that participated in the Journey development and in the learners’ literacy processes in the Newton Bello municipality. We used as a research instrument the semi-structured interview, containing inquiries that dealt with issues that are in line with our research objective, such as: the understanding of the Journey since its implementation; the development of their role (Literacy teacher and Class Coordinator) in the activities of the Conference and their assessment of the results of the Conference. The results of the study reveal that although the Official Evaluation Report of the Journey, carried out by state public agencies, indicates that 873 students were literate, there was a variation in the appropriation of literacy, and not all students were able to respond to the expectations required to be expressed in the guiding documents, however, we understand that this issue does not invalidate the reach of literacy for students. Furthermore, the process of implantation and organization, as well as the development of the Journey in the city, were characterized as fruitful political pedagogical moments for everyone involved.